An improved method of isolating salmonellae from contaminated desiccated coconut - Iveson, J. B. (1964)
A report is given on results obtained in the examination of desiccated coconut from Ceylon and the Philippines using two or three media in parallel, the aim being to investigate the efficacy of the enrichment medium introduced by Rappaport, Konforti, and Navon (1956). Although the claims of Rappaport et al. related only to examination of faeces the Rappaport enrichment medium has been found to give higher recovery rates of salmonella from desiccated coconut than the selenite and tetrathionate media. The differences are so striking as to justify an expansion of this work.